The portfolio implementations of prospective pre-school teachers in science and math education as an alternative evaluation instrument (The Sample Of Sabahattin Zaim University) - Parlakyıldız, Belgin (Sakarya Üniversitesi Eğitim Fakültesi, 2015)
Although the use of portfolio in the curriculum of teacher training and evaluation process is a common method, in recent years, it is a new trend in Turkey. The purpose of this study is to set forth an approach on using portfolio not only as an assessment tool based on constructivist approach but also as a teaching tool in the process of science and math education in preschool education. The document examination and observation methods of qualitative research were employed in this study. The study was conducted with second grade prospective preschool teachers (n=49). For this study, prospective teachers were asked to design two original experiments and materials for science and math education for children at the age of 4-6, to perform these experiments by them and children in a period of 14 weeks; and to perform these experiments at home and kindergarten in compliance with the target achievements. The experiments designed by prospective teachers were discussed with other prospective teachers in terms of being safe, economic and practicable. The experiments were performed by prospective teachers for two times; first at home and kindergarten, then at science classes. After the process of experiments and the applications of materials, the feedback obtained from children were re-evaluated by prospective teachers. Finally, the prospective teachers were asked to prepare portfolio involving their self-assessment regarding each step of the implementation process. As a result of this study, under the lights of portfolio implementations and evaluations, an approach was set forth towards the use of portfolio in the process of teacher training which paves the way for the usability of cognitive life skills at the highest level for teachers and suggestions were made.
Keywords: Preschool science and math education; Portfolio; Experiment; Material